4-HNE-induced cellular dysfunction from lipid peroxidation: a potential therapeutic target in diabetic cardiomyopathy - Jiang, Nan; Ma, Yanchun; Chen, Huijun; Li, Chengjia (Frontiers in Cell and Developmental Biology, 2026)
Diabetic cardiomyopathy (DCM) is one of the crucial causes leading to heart failure and adverse outcomes in patients with diabetes mellitus; however, effective strategies targeting its molecular pathological mechanisms and therapies are currently lacking. DCM is primarily characterized by early diastolic dysfunction, cardiomyocyte apoptosis, and fibrosis. Its disease progression is relatively insidious, eventually evolving into heart failure with preserved ejection fraction. The intrinsic metabolic environment of diabetes markedly exacerbates oxidative stress, and the accumulated polyunsaturated fatty acids within cardiomyocytes are highly susceptible to lipid peroxidation, leading to the excessive generation of 4-hydroxy-2-nonenal (4-HNE). The pivotal role of this reactive aldehyde in promoting the progression of DCM has been extensively demonstrated in animal, cellular, and clinical models. However, its subcellular targets and the underlying molecular mechanisms remain inadequately elucidated. Organelles, as central executors of diverse intracellular functions, may serve as potential sites of 4-HNE-induced interference and therapeutic targeting. This article focuses on the central role of 4-HNE in triggering energy depletion, calcium overload, autophagic flux blockade, and ferroptosis through its interactions among mitochondria, endoplasmic reticulum, lysosomes, and other organelles. On the basis of existing evidence, potentially translatable therapeutic avenues include ALDH2 activators, G protein–coupled receptor 40 (GPR40) agonists, mitochondria-targeted antioxidants and ferroptosis inhibitors. The aim is to provide a theoretical foundation and reference for the clinical identification of myocardial injury in DCM, model replication, and the development of targeted intervention strategies.